1997
DOI: 10.21900/j.inhs.v35.128
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Ingested Bismuth Alloy Shot in Game-farm Mallards

Abstract: In a 30-day study involving penned game-farm mallards (Anas platyrhynchos), no harmful health effects were detected from dosing with either six, No. 4, bismuth/tin (Bi/Sn) alloy shot or six, No. 4, steel (Fe) shot, as compared with sham (0 shot) dosing. Survival, hematocrit (Hct) values, body weight, and mean weights of kidneys, livers, gonads, and gizzards were not affected. Mean concentrations of nutritionally essential elements (calcium [Ca], phosphorous [P], magnesium [Mg], zinc [Zn], copper [Cu], Fe, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
4
2
1
Order By: Relevance
“…Ca deficiencies can result in bone disorders, reduced growth and performance, reduced egg production and hatchability, and eggshell thinning (Underwood 1981); however, values in our study were similar to those previously reported by other researchers (Sanderson et al 1997a;Fairbrother et al 1990). Mean kidney and liver Ca concentrations in Fe-dosed ducks in our study were similar to those Sanderson et al (1997a) reported for 0-and Fe-dosed Mallards.…”
Section: Calciumsupporting
confidence: 91%
See 3 more Smart Citations
“…Ca deficiencies can result in bone disorders, reduced growth and performance, reduced egg production and hatchability, and eggshell thinning (Underwood 1981); however, values in our study were similar to those previously reported by other researchers (Sanderson et al 1997a;Fairbrother et al 1990). Mean kidney and liver Ca concentrations in Fe-dosed ducks in our study were similar to those Sanderson et al (1997a) reported for 0-and Fe-dosed Mallards.…”
Section: Calciumsupporting
confidence: 91%
“…Kidney Cu levels were higher in Znas compared with Fe-dosed Mallards, and were higher in Zn-dosed ducks that survived to 30 days than in those that died during the experiment. Mean renal Cu concentrations in Fedosed ducks in our study were similar to those in 0-dosed ducks in a previous study (Sanderson et al 1997a); however, levels in Zn-dosed ducks were greatly elevated by comparison. French et al ( 1987) found that kidney Cu levels did not differ between Znand sham-dosed Mallards.…”
Section: Coppersupporting
confidence: 86%
See 2 more Smart Citations
“…Gao et al [29] evaluated the cytotoxicity of bismuth oxychloride (BiOCl) nanosheets, and they indicated that BiOCl had no cytotoxicity at low concentrations. Sanderson et al [30] reported no toxic effects of Bi shot embedded in the breast muscles of game-farm mallards. However, further investigations, including in vivo biocompatibility evaluations [31], are required to further understand and verify the biocompatibility of the zinc alloy containing Bi.…”
Section: Mechanical Propertiesmentioning
confidence: 98%